Calculation of ecological water requirements of urban rivers using a hydrological model: A case study of Beiyun River. (20th July 2020) - Zhang, Cheng; Wan, Zhongyu; Jing, Zhu; Zhang, Shanghong; Zhao, Yong
Abstract: The impacts of human activity lead to uncertainty and ambiguity when ecological water requirements (EWRs) are calculated based entirely on the current hydrological conditions of urban rivers, and the requirements for meeting the rivers' function will also be uncertain. Human activity and river function goals are important factors affecting EWRs. This paper discusses the definition of urban river EWRs and the uncertainties in the results of the calculation, and proposes a calculation method for urban river EWRs that is independent of human activity. The Beiyun River Basin, China, was selected for a case study. The EWRs of the Beiyun River were calculated by combining a precipitation frequency curve with a distributed hydrological model. The rationality of the calculated results was verified using the Tennant method and an evaporation plus seepage calculation for the river. The results of the calculation for the urban river EWRs method proposed in this paper are unique, and the total amount is not affected by human activities. With respect to wet, normal, and dry precipitation frequencies, the minimum, suitable, and ideal EWRs of the Beiyun River are 1.48 × 10 8 m 3, 2.79 × 10 8 m 3, and 3.57 × 10 8 m 3, respectively. The research conclusions are of great significance for the objective determination of the EWRs of urban rivers, and for promoting the appropriate planning and development of urban water.